Predictors of Post-Caesarean Surgical Site Infections at Mubende Regional Referral Hospital, Central Uganda: Prospective Cohort Study (July–September 2023) - Omara, Samuel; Kasujja, Musa; Okot, Geoffrey; Barageine, Justus Kafunjo (International Journal of Women's Health, 2024)
Post-caesarean surgical site infections (PCSSIs) significantly impact maternal morbidity, mortality, and healthcare costs in low- and middle-income countries, particularly in sub-Saharan Africa, where preventive measures are often inadequate. Despite this burden, data on PCSSIs in this context are limited. This study aimed to evaluate the incidence and factors associated with PCSSIs at Mubende Regional Referral Hospital.